Popular Religion in the Pala Period: Evidence from Iconographic Study of Four Female Deities from Northern Bengal - Sarker, Archishman (Religions of South Asia, 2021)
This article is an iconographic study of four sculptures from northern Bengal, of four female deities associated with Vajrayana Buddhist and Brahmanical cultic and religious practices: Aparajita, Rudra-Camunda, a snake goddess, and Mesavahini Sarasvati. They are housed at the Akshaya Kumar Maitreya Heritage Museum in North Bengal University, the Balurghat College Museum and the Coochbehar Palace Museum—three regional museums in northern West Bengal. Their provenance indicates that they were produced in the heart of the Varendri region, in present-day West Bengal (India) and Bangladesh. This study sheds light on the background in which these images were conceived—that of the co-existence of Vajrayana Buddhist practices and philosophy, several major and minor Brahmanical cults, and other local religious practices whose existence pre-dates both Buddhism and organized Brahmanism.